Grateful or not : the role of holistic thinking in interpreting suffering experiences - Tan, Phyllis Shi Hui (Nanyang Technological University, 2021)
I examined the causal roles of holistic thinking in meaning-making and gratitude in the context of suffering on Singaporean community participants. Specifically, I hypothesised that people who adopt holistic thinking are more likely to feel grateful for their suffering experiences and make meaning out of them. Two studies were captured in this report – a pilot study and a main study. The pilot study aimed to examine the effectiveness of the holistic thinking manipulation I developed. Results have shown that the holistic thinking manipulation was effective where participants who were led to process contradictory information were more holistic than participants who were in their natural state of mind. Following this, the main study aimed to further examine the effectiveness of the holistic thinking prime on a larger sample size and investigate the causal roles of holistic thinking in meaning-making and gratitude. Findings revealed a significant difference in the gratitude scores where participants in the holistic thinking condition felt more grateful for their suffering experiences compared to participants in the control condition. However, contrary to my hypotheses, the holistic thinking manipulation was not effective in the main study and participants who were in the holistic thinking condition did not differ from participants in the control condition in terms of their tendency to make meaning out of their suffering experiences. I concluded the report by discussing the limitations, implications and future directions of the study.